FEATURES OF TEACHING ENGLISH VOCABULARY TO PRIMARY SCHOOL CHILDREN (Conferencea, 2024)
This article reveals the methodological features of teaching English vocabulary as the main didactic activity when working with children. The article contains an approximate lexical theme, made up taking into account the age characteristics and interests of children 6-7 years old, and the types of exercises recommended for the presentation and consolidation of the studied material.